Temperatura e umidade do solo na co-inoculação na cultura da soja - Deak, Evandro Ademir (2017)
Biological nitrogen fixation (BNF) is very important for the soybean crop, since it is almost entirely responsible for the nitrogen (N) supply to the plants. The bacteria responsible for this process in the soybean crop belong to the genus Bradyrhizobium, and for this supply of N to occur properly, it is important that the abiotic factors related to BNF are favorable. The objective of this study was to verify the temperature and soil moisture ranges of the best agronomic performance of the tested inoculations. Laboratory, greenhouse and field experiments were carried out to verify the best soil temperature and humidity conditions for the bacteria, as well as to evaluate the agronomic performance of Bradyrhizobium spp. When applied in isolation (standard inoculation), or in combination with Azospirillum brasilense (co-inoculation) and with the addition of a rooting agent. The inoculation treatments were: noninoculated (NI); Inoculation with Bradyrhizobium [I (Brady)]; Rooting machine (E); Inoculation with Bradyrhizobium + rooting (I+E); Co-inoculation with Bradyrhizobium + Azospirillum brasilense (I+Azo); Co-inoculation with Bradyrhizobium + Azospirillum brasilense + rooting (I+Azo+E). The experiment in the seed laboratory was performed by subjecting all treatments at different temperatures, 15, 20, 25, 30 and 35ºC. For the greenhouse experiment and the field, another treatment was added, the non-inoculated with nitrogen supply (NI+N). In greenhouse, the plants were cultivated under different levels of soil moisture, 25, 50, 75 and 100% of the water retention capacity of the soil. Two experiments were carried out on the field, which consisted in the use of different inoculations, with or without water use in the sowing furrow (200 L ha-1). Co-inoculation promotes improvements in the root system of soybean, in relation to length, volume, surface area and root diameter. It is higher than the uninoculated control in the temperature range between 20 and 30ºC. Co-inoculation increases nodulation of soybean plants, in terms of nodule dry mass and nodule number. Between 56 and 96% of the water retention capacity of the soil, the co-inoculation obtained higher averages when compared to the standard inoculation. The rooting did not provide improvements in the root system and nodulation of soybean plants. In addition to causing reduction in root length and surface area when used together with co-inoculation. The use of water in the sowing furrow does not interfere with nodulation and soybean productivity components. Co-inoculation increases nodulation of soybean plants, in terms of nodule dry mass and nodule number.